Friday

August 29, 2014

August 29, 2014

Posted by **Jake** on Monday, October 22, 2012 at 12:18pm.

- Calculus -
**Steve**, Monday, October 22, 2012 at 2:14pmsince log(ab) = log(a) + log(b), this would be (assuming logs to base 2)

log(4) + log(x^2) + log(2^x)

= 2 + 2log(x) + x

**Related Questions**

math - solve the equation log2(x+4)-log4x=2 the 2 and 4 are lower than the g ...

Logarithms - I'm working on logarithmic equations and I'm stuck on how my book ...

calculus - Solve the equations i) log2(x + 2) + log2 x = 3. ii) 25^x + 5^x+1 + 6...

add maths - Given that log2 3=h and log2 5=k, express log2 0.45 in terms of h ...

calculus - log2^24 - log2^3 = log5^x what is X? thanks

Math - Logarithmic - Solve: 2^(5x-6) = 7 My work: log^(5x-6) = log7 5x - 6(log2...

math30 - 1.Use the laws of logarithms to express log2 (6) – log2 (3) + 2log2 (...

Algebra 2 - solve log2(3x-1)-log2(x-1)=log2(x+1) i have absolutely no idea how ...

math - simplify 2log4(9)-log2(3)

Math Algebra 2 - How do I put log in a TI-84 calculator. #1.Express the ...